Safety of Treatment Regimens Containing Bedaquiline and Delamanid in the endTB Cohort . (13th January 2022) - Hewison, Catherine; Khan, Uzma; Bastard, Mathieu; Lachenal, Nathalie; Coutisson, Sylvine; Osso, Elna; Ahmed, Saman; Khan, Palwasha; Franke, Molly F; Rich, Michael L; Varaine, Francis; Melikyan, Nara; et al.
Abstract: Background: Safety of treatment for multidrug-resistant tuberculosis (MDR/RR-TB) can be an obstacle to treatment completion. Evaluate safety of longer MDR/RR-TB regimens containing bedaquiline and/or delamanid. Methods: Multicentre (16 countries), prospective, observational study reporting incidence and frequency of clinically relevant adverse events of special interest (AESIs) among patients who received MDR/RR-TB treatment containing bedaquiline and/or delamanid. The AESIs were defined a priori as important events caused by bedaquiline, delamanid, linezolid, injectables, and other commonly used drugs. Occurrence of these events was also reported by exposure to the likely causative agent. Results: Among 2296 patients, the most common clinically relevant AESIs were peripheral neuropathy (26.4%), electrolyte depletion (26.0%), and hearing loss (13.2%) with an incidence per 1000 person months of treatment, 1000 person-months of treatment 21.5 (95% confidence interval [CI]: 19.8–23.2), 20.7 (95% CI: 19.1–22.4), and 9.7 (95% CI: 8.6–10.8), respectively. QT interval was prolonged in 2.7% or 1.8 (95% CI: 1.4–2.3)/1000 person-months of treatment. Patients receiving injectables (N = 925) and linezolid (N = 1826) were most likely to experience events during exposure. Hearing loss, acute renal failure, or electrolyte depletion occurred in 36.8% or 72.8 (95% CI: 66.0–80.0) times/1000 person-months of injectable drug exposure. Peripheral neuropathy, optic neuritis, and/or myelosuppression occurred in 27.8% or 22.8 (95% CI: 20.9–24.8) times/1000 patient-months of linezolid exposure. Conclusions: AEs often related to linezolid and injectable drugs were more common than those frequently attributed to bedaquiline and delamanid. MDR-TB treatment monitoring and drug durations should reflect expected safety profiles of drug combinations. Clinical Trials Registration: NCT02754765. Abstract : Systematic adverse events (AEs) reporting during the endTB observational study showed that AEs related to linezolid and injectable drugs were frequent during multidrug-resistant tuberculosis treatment containing bedaquiline and delamanid, whereas QT prolongation was uncommon. AE monitoring should be adapted accordingly.